Student academic performance in principles and application of financial reporting standards 1 paper / Zuhariah Husin …[et al.] - Husin, Zuhariah; Abd Wahab, Roslan; Mohd Din, Norlaila; Mat Bahari, Anis Barieyah; Md Zeni, Syahida (2014)
This study was undertaken to identify and highlight the possible factors affecting students' performance in the FAR400 of the Bachelor of Accountancy (BAcc) in University Technology MARA (UiTM) Pahang. The mediocre performance and lack of excellent grades in this course were discussed and debated by the faculty members and lecturers alike. Students enrolling in any program are expected to excel in the core courses of the program and since FAR400 paper is one of such courses of the BAcc program, a respectable percentage of students if not the majority are expected to excel in the course by obtaining excellent grades A+, A or at least A-. However this is not the case of FAR400 paper. Survey questionnaires were distributed to second and final year students of BAcc to identify the possible factors affecting their performance in the said paper. The respondents' feedback identified factors namely motivation, mathematics ability, English proficiency, interest on accounting subject, prior knowledge on accounting, time management, study skills, class participation, effort level and study habit. The findings indicate that students are facing a number of critical issues especially bad study habits (mean of 2.41), low effort level (2.44) and inactive class participation (2.46). It was also found that prior knowledge, interest on accounting subject, motivation and class participation is positively correlated to the student excellent performance in the FAR400 paper. Consequently, appropriate recommendations are made to help students and lecturers alike in improving the performance of FAR400.